2017
DOI: 10.1016/j.jvs.2016.05.096
|View full text |Cite
|
Sign up to set email alerts
|

Fast-degrading bioresorbable arterial vascular graft with high cellular infiltration inhibits calcification of the graft

Abstract: Objective Bioresorbable vascular grafts are biologically active grafts which are entirely reconstituted by host-derived cells through an inflammation-mediated degradation process. Calcification is a detrimental condition that can severely impact graft performance. Therefore, prevention of calcification is of great importance to the success of bioresorbable arterial vascular grafts. The objective of this study is to test whether fast degrading bioresorbable arterial grafts with high cellular infiltration will i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 27 publications
(29 reference statements)
3
34
0
1
Order By: Relevance
“…After 28 days, however, expression levels had declined to values that are equivalent to that of native aorta and remained constant throughout the course of the study, indicating a favorable down-regulation of TGF-β expression to avoid fibrosis. This is in line with recent studies, which demonstrated that timely scaffold degradation is essential to prevent fibrotic calcification of TEVGs in the arterial circulation [ 7 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…After 28 days, however, expression levels had declined to values that are equivalent to that of native aorta and remained constant throughout the course of the study, indicating a favorable down-regulation of TGF-β expression to avoid fibrosis. This is in line with recent studies, which demonstrated that timely scaffold degradation is essential to prevent fibrotic calcification of TEVGs in the arterial circulation [ 7 , 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…In order to inhibit the calcification of the graft, Sugiura et al [24] also combined the two methods of casting and electrospinning. Two versions of bioresorbable vascular grafts were created: slow-degrading (SD) grafts and fast-degrading (FD) grafts.…”
Section: Castingmentioning
confidence: 99%
“…How to adjust the mechanical properties of degrading vascular scaffolds not only maintaining the vascular integrity, but also matching with the regenerated neovascular tissue strength is a significant qualification for these eligible graft prostheses. Furthermore, it is noteworthy that the calcification would often lessen the long‐term efficacy of small‐diameter TEVGs …”
Section: Introductionmentioning
confidence: 99%